Increased microchimeric CD4+ T lymphocytes in peripheral blood from women with systemic sclerosis - Artlett, Carol M (Clinical immunology (Orlando, Fla.), 2002)
Recent studies have demonstrated the presence of microchimeric cells in peripheral blood and skin lesions from patients with systemic sclerosis (SSc). In a previous study we found that some peripheral blood CD3+ cells from female patients with SSc contained male DNA. Here, peripheral blood samples from 47 patients with SSc (30 with diffuse cutaneous SSc and 17 with limited cutaneous SSc) and 22 healthy controls were sorted for CD4+ and CD8+ T cells. Both positively and negatively selected populations were analyzed for male DNA by quantitative PCR. Analysis of Y chromosome sequences in the sorted cells demonstrated the presence of microchimerism in 82.9% of SSc patients compared to 63.6% of controls. The numbers of CD4+ and CD8+ T cells were found to be significantly higher in the SSc patients than in controls. Furthermore, patients with dcSSc were observed to have significantly more CD4+ microchimeric T cells than the controls. In the CD8+ T-cell population, there was a trend toward more microchimeric cells in the patients but this did not reach significance. These results support the hypothesis that microchimeric CD4+ T cells may be involved in the pathogenesis of SSc